La-based perovskites for capacity enhancement of Li–O2 batteries - Hsu, Bing-Ze; Lai, Jun-Kai; Lee, Yi-Hsuan (Frontiers in Chemistry, 2023)
Li–O2 batteries are a promising technology for the upcoming energy storage requirements because of their high theoretical specific energy density of 11,680 Wh kg−1. Currently, the actual capacity of Li–O2 batteries is much lower than this theoretical value. In many studies, perovskites have been applied as catalysts to improve the air electrode reactions in Li–O2 batteries. The effects of structure and doping on the catalytic activity of perovskites are still unclear. La1-xSrxCoO3-δ (x = 0.1, 0.3, and 0.5) and La0.9Sr0.1YbO3-δ mixed with carbon black (Vulcan XC500 or Super P) were used as air electrode catalysts. Electrochemical characterizations were conducted using a Swagelok-type cell. The charge–discharge capacity and cyclic voltammetry (CV) performance were investigated in this study. The La1-xSrxCoO3-δ (x = 0.1, 0.3, and 0.5) is a suitable cathode catalyst for Li–O2 batteries. In this study, the La0.5Sr0.5CoO3-δ/Super P cathode demonstrated the highest discharge capacity (6,032 mAh g−1). This excellent performance was attributed to the large reaction area and enhanced Li2CO3 generation.